Raising primary school enrollment in developing countries: the relative importance of supply and demand - Handa, Sudhanshu (International Food Policy Research Institute, 1999)
Few policies are as universally accepted as raising primary school enrolment in developing countries, but the policy levers for achieving this goal are not straight forward. This paper merges household survey data with detailed school supply characteristics from official sources, in order to estimate the relative impact of demand- and supply-side determinants of rural primary school enrolment in Mozambique. Policy simulations based on a set of “plausible” interventions show that demand-side interventions, particularly those aimed at raising rural adult literacy, will have the biggest impact on primary school enrolment rates.